NPY derived from AGRP neurons controls feeding via Y1 and energy expenditure and food foraging behaviour via Y2 signalling - Yue Qi; Nicola J. Lee; Chi Kin Ip; Ronaldo Enriquez; Ramon Tasan; Lei Zhang; Herbert Herzog (Elsevier, 2022)
Objective: Aguti-related protein (AGRP) neurons in the arcuate nucleus of the hypothalamus (ARC), which co-express neuropeptide Y (NPY), are key regulators of feeding and energy homeostasis. However, the precise role NPY has within these neurons and the specific pathways that it control are still unclear. In this article, we aimed to determine what aspects of feeding behaviour and energy homeostasis are controlled by NPY originating from AGRP neurons and which Y-receptor pathways are utilised to fulfil this function. Methods: Novel conditional Agrpcre/+;Npylox/lox knockout mice were generated and comprehensively phenotyped, both under standard chow as well as high-fat-diet conditions. Designer receptor exclusively activated by designer drugs (DREADD) technology was used to assess the altered responses on feeding and energy homeostasis control in the absence of NPY in these neurons. Rescue experiments utilising Npy1r- and Npy2r-selective NPY ligands were performed to assess which component of the energy homeostasis control is dependent by which specific Y-receptor pathway. Results: We show that the specific deletion of Npy only in AGRP neurons leads to a paradoxical mild obese phenotype associated with reduced locomotion and energy expenditure and increased feeding and Respiratory Quotient (RQ) that remain elevated under a positive energy balance. The activation of Npy-deficient AGRP neurons via DREADD's is still able to drive feeding, yet with a delayed onset. Additionally, Clozapine-N-oxide (CNO) treatment reduces locomotion without impacting on energy expenditure. Rescue experiments re-introducing Npy1r- and Npy2r-selective NPY ligands revealed that the increased feeding and RQ are mostly driven by Npy1r, whereas energy expenditure and locomotion are controlled by Npy2r signalling. Conclusion: Together, these results demonstrate that NPY originating from AGRP neurons is not only critical to initiate but also for continuously driving feeding, and we for the first time identify which Y-receptor controls which pathway.